Sensorial perception of astringency: oral mechanisms and current analysis methods - Pires, Mariana A. (2020)
Understanding consumers’ food choices and the psychological processes involved in their preferences is crucial to promote more mindful eating regulation and guide food design. Fortifying foods minimizing the oral dryness, rough, and puckering associated with many functional ingredients has been attracting interest in understanding oral astringency over the years. A variety of studies have explored the sensorial mechanisms and the food properties determining astringency perception. The present review provides a deeper understanding of astringency, a general view of the oral mechanisms involved, and the exciting variety of the latest methods used to direct and indirectly quantify and simulate the astringency perception and the specific mechanisms involved.